Diagnostic Accuracy of Point-of-Care Testing for Diabetic Ketoacidosis at Emergency-Department Triage: β-Hydroxybutyrate versus the urine dipstick - Arora, Sanjay (American Diabetes Association, 2011)
OBJECTIVE: In the emergency department, hyperglycemic patients are screened for diabetic ketoacidosis (DKA) via a urine dipstick. In this prospective study, we compared the test characteristics of point-of-care β-hydroxybutyrate (β-OHB) analysis with the urine dipstick. RESEARCH DESIGN AND METHODS: Emergency-department patients with blood glucose ≥250 mg/dL had urine dipstick, chemistry panel, venous blood gas, and capillary β-OHB measurements. DKA was diagnosed according to American Diabetes Association criteria. RESULTS: Of 516 hyperglycemic subjects, 54 had DKA. The urine dipstick had a sensitivity of 98.1% (95% CI 90.1–100), a specificity of 35.1% (30.7–39.6), a positive predictive value of 15% (11.5–19.2), and a negative predictive value of 99.4% (96.6–100) for DKA. Using the manufacturer-suggested cutoff of >1.5 mmol/L, β-OHB had a sensitivity of 98.1% (90.1–100), a specificity of 78.6% (74.5–82.2), a positive predictive value of 34.9% (27.3–43), and a negative predictive value of 99.7% (98.5–100) for DKA. CONCLUSIONS: Point-of-care β-OHB and the urine dipstick are equally sensitive for detecting DKA (98.1%). However, β-OHB is more specific (78.6 vs. 35.1%), offering the potential to significantly reduce unnecessary DKA work-ups among hyperglycemic patients in the emergency department.